How Does Classical Background Music During the Independent Work of High Ability Students Affect Their Learning, Behaviour and Perception of Mathematics - Langstone, Andrew (2012)
How Does Classical Background Music During the Independent Work of High Ability Students Affect Their Learning, Behaviour and Perception of Mathematics